Fungi associated with pods and seeds during the R6 and R8 stages of four soybean cultivars in southwestern Indiana - Baird, R.E.; Abney, T.S.; Mullinix, B.G.. (Phytoprotection, 2001)
A total of 6,403 isolates of fungi were identified from soybean pods and seeds collected late in the 1992 and 1993 growing season (R6 and R8 soybean growth stages). The majority of fungi consisted of Deuteromycetes (95.5%) followed by Ascomycetes (0.9%). Common fungal genera isolated during the study included Phomopsis, Alternaria, Cercospora, and Colletotrichum (= Glomerella) . Cercospora and Phomopsis were identified more commonly from pods and seeds at harvest maturity (R8) than at the greenbean stage of development (R6). However, isolation frequencies of Colletotrichum were greater from tissues collected at R6 than at R8. Isolation frequencies compared between pod and seed tissue were similar for almost all the fungi except Alternaria, Phoma, and Nigrospora. The primary pathogenic species identified from the Diaporthe/Phomopsis complex were D. phaseolorum var. caulivora and D. phaseolorum var. sojae at 28.2% of the total isolation frequencies compared to D. phaseolorum var. meridionalis and Phomopsis longicolla that were identified from 1% of the total samples. The pod tissue harbored greater numbers of fungi than seeds during this study. In statistical comparisons of the peduncle, middle, and stylar regions from pods, no differences in isolation frequencies were found for the cultivars tested regardless if pod tissues or seeds were compared. In summary, the percent isolation frequency of pathogenic fungi from pod and seed at R6 was an effective indicator of the potential for increased disease severity. Furthermore, the significantly greater occurrence of D. phaseolorum var. caulivora and D. phaseolorum var. sojae compared to the other Phomopsis/Diaporthe spp. (e.g. D. phaseolorum var. meridionalis) in southern Indiana will enable scientists to continue to concentrate their breeding efforts for resistance to control these two major pathogens.